Proinflammatory cytokine production from NOK-SI keratinocytes after exposure to denture adhesives - Perin Leite, Andressa Rosa [UNESP]; de Oliveira Júnior, Norberto Martins [UNESP]; Mendoza Marin, Danny Omar [UNESP]; Compagnoni, Marco Antonio [UNESP]; Pero, Ana Carolina [UNESP] (Elsevier, 2018)
Statement of problem: Although the cytotoxicity of denture adhesives has been widely assessed, data on the release of proinflammatory cytokines from oral epithelial cells are still scarce. Purpose: The purpose of this in vitro study was to evaluate the proinflammatory cytokines interleukin (IL) 1β IL-6, and tumor necrosis factor α (TNF-α) released from human oral keratinocytes after exposure to denture adhesives. Material and methods: Eluates of the Ultra Corega cream, Corega powder Fixador Ultra, and Corega strip denture adhesives were created at 1% wt/vol after 24 hours of exposure in a Dulbecco modified Eagle medium culture. The release of IL-1β IL-6, and TNF-α was measured using a sandwich enzyme-linked immunosorbent assay after the oral epithelial cells (NOK-SI) had been exposed to the eluates for 3, 6, and 24 hours (n=6). Results: IL-1β release from the strip was higher at 3 hours compared with the control (Bonferroni post hoc test, P=.016). IL-6 releases from the cream and powder denture adhesives at 6 and 24 hours were higher than for the controls (Bonferroni post hoc test, P<.05). TNF-α release was not detectable in some groups and periods. Conclusions: In long periods, denture adhesive strips do not induce any change on cytokine release from human oral keratinocytes.